A study on the impact of anthropogenic and geogenic factors on groundwater salinization and seawater intrusion in Gaza coastal aquifer, Palestine: An integrated multi-techniques approach - Abu Al Naeem, Madhat Farouk; Yusoff, Ismail; Ng, Tham Fatt; Maity, Jyoti Prakash; Alias, Yatimah; May, Raksmey; Alborsh, Hussam (Elsevier, 2019)
Groundwater salinization and seawater intrusion (SWI) is a widespread issue affecting many arid and semi-arid coastal regions such as the Gaza Strip, Palestine. The aims of this study were to acquire a comprehensive understanding of the role of anthropogenic and geogenic factors on controlling groundwater salinization and to assess the SWI extent and the hydrogeochemical processes involved. To achieve these objectives, an integrated approach of hydrogeological, hydro-geochemical, and statistical techniques combined with geostatistical semi-variogram modeling was applied on a comprehensive dataset using software (Stata/SE 12, ArcGIS 10.4 and Surfer 16 Golden software Inc.). The results indicate that the intensive groundwater exploitation creates a huge cone of depression covering 75% of the study area and reduces the water table to as much as 19 m below mean sea level (BMSL) at 4.3 km from the shoreline, causing SWI. The extension of SWI depends strongly on the lithological characters of the area. It reached to 48.6% with inland encroachment around 3 km in the northern area. Moreover, the spatial distribution and high pumping rates have significantly influenced the spatial pattern of SWI. Hierarchical cluster analysis (HCA) yielded nine distinct hydrogeochemical signature clusters. Factor analysis (FA) approves that the high groundwater salinization was the result of three main factors loadings that account for 83.86% of the total variance These factors are F1 as salinization (mainly SWI), F2 as mixing of sewage invasion and water hardness and F3 as carbonate dissolution. Factors scores clarify the areas which are more impacted by the different hydro-geochemical processes. Ionic deltas and ionic ratios reveal the dominance of reverse ion exchange process. Moreover, the distinct surplus of sulfate along the sea shoreline may indicate the existence of old seawater transgression. This integrated approach should be useful for efficient groundwater management of the Gaza coastal aquifer system as well as for other similar aquifers. © 2019 Elsevier Ltd